Development of Summative Assessment Instruments for the Affective Aspects of Learning History - Syarifah Syarifah (AL-ISHLAH: Jurnal Pendidikan, 2023)
Instruments for measuring both the affective and psychomotor aspects of teaching are required. The study's overarching goal is to create a reliable and valid assessment tool for measuring affective competency (values contained in history). Nine hundred thirty-five students from Medan's XI Social Sciences high school participated as research subjects. An affective aspect assessment sheet, which is a questionnaire with various statements to gauge affective aspects, was used to collect research data. To compare measurement models and make it simpler to analyze model correctness, structural equation modelling (SEM) analysis with first- and second-order components was employed in the data analysis. The findings of the first-order confirmatory factor analysis using the ML (maximum likelihood) technique indicated that all items had a correlation coefficient greater than 0.32, and the results of testing using the model had a significance level of 0.0001, according to the research analysis. The structural equation model (SEM) findings, with support from second-order structures, are also estimated with adequate theoretical confidence. The construct reliability (CR) and variance extract (VE) coefficients indicate that the designed instrument complied with the reliability coefficient acceptability limits of 0.70 for CR and 0.50 for VE. The development process resulted in an affective competency assessment tool with 84 valid and reliable items spread across 5 dimensions and 14 indicators. The instruments created were therefore shown to be valid and reliable for assessing affective aspects of learning history. The findings of this study are utilized to diagnose student potential, particularly concerning affective components, so that students are aware of their strengths and weaknesses. The findings of this study are utilized by stakeholders as input for policymaking, particularly in the area of education.